Early childhood home-based programmes and school violence: evidence from Brazil. Issue 2 (17th February 2022) - Wink Junior, Marcos Vinicio; Ribeiro, Felipe Garcia; Paese, Luis Henrique Zanandrea
ABSTRACT: This paper evaluates the impacts of a Brazilian home-based programme on violent behaviour of elementary school students. To identify the causal impact, it explores the variation between schools with potentially treated students and the municipalities that implemented the programme over the years. The results suggest a reduction in verbal or physical abuse, theft or robbery, and attack or threat by more than 5 percentage points in schools with treated students. There is also evidence that the effects are greater the sooner children participate in the programme, meaning that early years interventions can be an effective policy to reduce school violence.